Severe Cardiac Toxicity Induced by Cancer Therapies Requiring Intensive Care Unit Admission - Montisci, Andrea; Palmieri, Vittorio; Liu, Jennifer E.; Vietri, Maria T.; Cirri, Silvia; Donatelli, Francesco; Napoli, Claudio (Frontiers in Cardiovascular Medicine, 2021)
A steadying increase of cancer survivors has been observed as a consequence of more effective therapies. However, chemotherapy regimens are often associated with significant toxicity, and cardiac damage emerges as a prominent clinical issue. Many mechanisms sustain chemotherapy-induced cardiac toxicity: direct myocytes damage, arrhythmias induction, coronary vasospasm, accelerated atherosclerosis. Anthracyclines are the most studied cardiotoxic drugs and represent a clinical model for cardiac damage induced by chemotherapy. In patients suffering from advanced heart failure (HF) because of chemotherapy-related cardiomyopathy, when refractory to optimal medical therapy, mechanical circulatory support or heart transplantation represent an effective treatment. Here, the main mechanisms of cardiac toxicity induced by cancer therapies are analyzed, with a focus on patients requiring intensive care unit (ICU) admission during the course of the disease because of acute cardiac toxicity; takotsubo syndrome; acute-on-chronic HF in patients suffering from chemotherapy-induced cardiomyopathy. In a subset of patients, cardiac toxicity can be acute and life-threatening, leading to overt cardiogenic shock. The management of critically ill cancer patients poses a unique challenge and requires a multidisciplinary approach. Moreover, no etiologic therapy is available, and only supportive measures can be implemented.